The Application of Construct 2 Application the Development of Interactive Digital Modules as Learning Media in Effective Communication Course in Education PG PAUD FIP UNIMED - Elya Siska Anggraini; Aman Simaremare; Wan Nova Listia (Universitas Muhammadiyah Enrekang, 2023)
This study aims to (1) develop and implement the construct 2 application as an interactive digital module, (2) determine the feasibility of the construct 2 application as an interactive learning media, (3) determine the assessment of students, media experts and material experts. This research is a type of method used by Research and Development (RnD) with the ADDIE development model. which includes analysis, design, development, implementation, and evaluation, but only carried out up to stage four, namely implementation. Data collection techniques were carried out using a questionnaire. In general, the results of the assessment of the material aspect validation test are classified as Good with a total score of 88 and the range of values and media aspect validation are also classified as Very Good category, namely 93 with an average value of 4.65. So that the Application of Construct 2 Application-Based Interactive Learning Media in Effective Communication Courses in Education PG PAUD FIP UNIMED is worthy of being used as a learning medium and independent learning resource. Keywords: Construct 2 Application, Effective Communication in Education, Interactive Learning Media, PG PAUD